2021
DOI: 10.1186/s12884-020-03498-3
|View full text |Cite
|
Sign up to set email alerts
|

The Iranian version of theory-based intention for cesarean section (IR-TBICS) scale: development and first evaluation

Abstract: Background The rate at which mothers experience a cesarean section in the absence of medical signs is growing worldwide. Women’s beliefs and intentions play an essential role in the request or choice of a delivery method. At present, there is no comprehensive, validated scale for assessing pregnant women’s beliefs about cesarean section in the Iranian population. This study was performed to develop and assess the validity and reliability of the intention-based cesarean section scale using the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In addition, a part of this increase might be due to the change in individuals' attitudes toward childbirth approaches. Other studies showed that emotional causes, misconceptions and wrong mental norms in Iranian mothers, sociocultural, religious, and economic customs, and poorly understood behavioral control were the most important causes in choosing the type of delivery (19). Currently, 6 -17% of all births occurring through CS worldwide are based on the mother's request (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a part of this increase might be due to the change in individuals' attitudes toward childbirth approaches. Other studies showed that emotional causes, misconceptions and wrong mental norms in Iranian mothers, sociocultural, religious, and economic customs, and poorly understood behavioral control were the most important causes in choosing the type of delivery (19). Currently, 6 -17% of all births occurring through CS worldwide are based on the mother's request (11).…”
Section: Introductionmentioning
confidence: 99%